Komplexe Schadstoffflussanalysen aus geochemischer Sicht als Grundlage für eine nachhaltige Stadtplanung - Stüben, Doris; Norra, Stefan (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
Accompanying the global trend towards urbanisation are increasing levels of environmental pollution resulting from the constantly rising volumes of harmful substances being emitted. Most severely affected by these are the soil, water courses, the atmosphere, flora and fauna — and the quality of life for humans. In order to safeguard quality of life, there is a pressing need for extensive and comprehensive knowledge of pollutant fluxes, culminating in an integrated strategy for pollutant management, in particular to protect the environment in towns and cities through the effective regulation of fluxes of harmful substances. The authors draw on cases studies covering specific aspects of material-flow analysis and define the key parameters in an attempt to describe an interdisciplinary approach towards the development of a management system for harmful substances applicable in urban areas.
Keywords: Article